Analisis Harga dan Gaya Hidup terhadap Minat Beli Handphone Iphone Second Like New - Darto, Cahyo Novi Tri; Irawan, Hengki; Susanto, Rindang (STIES ALIFA, 2024)
This study aims to analyze the influence of price and lifestyle on the purchase intention of second like-new iPhones in Bandar Lampung City, specifically among consumers of Nano Store. The rapid development of technology and the increasing public demand for smartphones have made the iPhone one of the most sought-after products due to its quality and prestige. However, the high price of new iPhones has led some consumers to opt for second like-new iPhones, which are considered more affordable yet still functional. This research employs a quantitative approach using a survey method with 100 respondents. The results show that the price variable has a negative and significant effect on purchase intention (significance value 0.002 < 0.05), indicating that the lower the price, the higher the purchase intention. Meanwhile, lifestyle has a positive and significant effect on purchase intention (significance value 0.000 < 0.05), suggesting that the higher a person's lifestyle level, the greater their intention to purchase a second like-new iPhone. Simultaneously, price and lifestyle significantly influence purchase intention, contributing 44.4% to the purchase intention variable. These findings indicate that second like-new iPhones have become a rational and prestigious choice for urban communities, primarily due to affordable pricing and the need to align with today’s digital lifestyle